2009
DOI: 10.2478/10004-1254-60-2009-1936
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Bleomycin Lethality in HeLa and V79 Cells by Bee Venom

Abstract: This study investigated possible growth-inhibiting effects of bee venom applied alone or in combination with a cytotoxic drug bleomycin on HeLa and V79 cells in vitro based on clone formation, cell counting, and apoptosis. Melittin, the key component of bee venom, is a potent inhibitor of calmodulin activity, and also a potent inhibitor cell growth and clonogenicity. Intracellular accumulation of melittin correlates with the cytotoxicity of antitumour agents. Previous studies indicated that some calcium antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 35 publications
1
23
1
4
Order By: Relevance
“…The same result was observed in Chinese hamster lung fibroblasts subjected to cotreatment with BV and BLM [25]. Moreover, the inhibitory impact of BV solely on cell viability and proliferation was observed in several types of nontumor isolated cells (i.e., normal human lymphocytes) and cell lines (human embryonic kidney HEK-293 cells and normal Hef fibroblasts), as well as tumor cell lines (human laryngeal HEp-2 and cervical carcinoma HeLa cells and their drug resistant sublines, breast adenocarcinoma MCF-7 cells, colon adenocarcinoma SW620 cells, and glioblastoma A1235 cells) [38, 39].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The same result was observed in Chinese hamster lung fibroblasts subjected to cotreatment with BV and BLM [25]. Moreover, the inhibitory impact of BV solely on cell viability and proliferation was observed in several types of nontumor isolated cells (i.e., normal human lymphocytes) and cell lines (human embryonic kidney HEK-293 cells and normal Hef fibroblasts), as well as tumor cell lines (human laryngeal HEp-2 and cervical carcinoma HeLa cells and their drug resistant sublines, breast adenocarcinoma MCF-7 cells, colon adenocarcinoma SW620 cells, and glioblastoma A1235 cells) [38, 39].…”
Section: Discussionsupporting
confidence: 79%
“…However, BLM increases the risk for a life threating lung injury and a wide variety of chromosomal aberrations in noncancerous cells [21]. In addition to its diverse curative applications, BV has been proven to be a useful compound in potentiating the apoptotic killing capacity of some chemotherapeutic agents such as BLM in cancer cell lines [25, 36]. However, Park et al [37] recorded the antiapoptotic effect of BV against tumor necrosis factor (TNF)- α with actinomycin D-induced apoptosis in normal hepatocyte cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orsolic [29], while investigating cytotoxic effects of bee venom applied alone or in combination with the DNA-damaging drug bleomycin on HeLa and V79 cells, found that bleomycin caused a dose-dependent decrease in cell survival. When used with a non-lethal dose of the BV, its lethal effect was potentiated.…”
Section: Discussionmentioning
confidence: 99%
“…When used with a non-lethal dose of the BV, its lethal effect was potentiated. The author inferred that BV, by preventing repair of damaged DNA, increases bleomycin lethality and inhibited recovery from bleomycin-induced damage [29]. …”
Section: Discussionmentioning
confidence: 99%